2023
DOI: 10.3847/1538-4357/accbbe
|View full text |Cite
|
Sign up to set email alerts
|

The Assembly of Black Hole Mass and Luminosity Functions of High-redshift Quasars via Multiple Accretion Episodes

Abstract: The early evolution of the quasar luminosity function (QLF) and black hole mass function (BHMF) encodes key information on the physics determining the radiative and accretion processes of supermassive black holes (BHs) in high-z quasars. Although the QLF shape has been constrained by recent observations, it remains challenging to develop a theoretical model that explains its redshift evolution associated with BH growth self-consistently. In this study, based on a semianalytical model for the BH formation and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 213 publications
3
25
0
Order By: Relevance
“…They show constant values with a mean at 0.01 ∼ 0.15 over a wide BH mass range of M M 7.5 log 9 BH  < < , implying the phase of active accretion is occurring throughout the less-massive SMBH population without preferences on the BH mass. That active fractions are consistent with the values evaluated with the X-ray-selected AGNs in the deep survey fields (e.g., Bongiorno et al 2012Bongiorno et al , 2016Georgakakis et al 2017), and with the semianalytical model for the BH formation and growth (e.g., Li et al 2022). Again, the increase beyond M M log 9 BH  > is highly uncertain because the total BHMFs are evaluated with the extrapolated M BH -M Bulge or M BH -M star relations.…”
Section: ´+supporting
confidence: 79%
“…They show constant values with a mean at 0.01 ∼ 0.15 over a wide BH mass range of M M 7.5 log 9 BH  < < , implying the phase of active accretion is occurring throughout the less-massive SMBH population without preferences on the BH mass. That active fractions are consistent with the values evaluated with the X-ray-selected AGNs in the deep survey fields (e.g., Bongiorno et al 2012Bongiorno et al , 2016Georgakakis et al 2017), and with the semianalytical model for the BH formation and growth (e.g., Li et al 2022). Again, the increase beyond M M log 9 BH  > is highly uncertain because the total BHMFs are evaluated with the extrapolated M BH -M Bulge or M BH -M star relations.…”
Section: ´+supporting
confidence: 79%
“…The virial BH mass estimate we present above now shows that this low-luminosity AGN is by far the least massive BH known in the Universe at the end of cosmic reionization. The modest Eddington ratio of CEERS 2782 suggests that this AGN has been identified after its rapid accretion mode has ended, although it is possible that the system will experience future bursts of heavy accretion (Li et al 2023).…”
Section: The M Bh -L Bol Distributionmentioning
confidence: 99%
“…These ultrarare systems, which formed in biased regions of the early Universe, place limited constraints on the BH seed population, as they would have undergone sustained episodes of exponential growth, even for the most massive predicted seeds, thereby erasing the imprint of the initial seed mass distribution (e.g., Tanaka & Haiman 2009;Volonteri 2010). A complementary approach is to search for lower-luminosity quasars hosting SMBHs with masses closer to the predicted seed mass range at the earliest epochs possible (Somerville et al 2008;Valiante et al 2016;Ricarte & Natarajan 2018;Yung et al 2021;Li et al 2023). Several deep optical surveys have attempted to do this by reaching a dex fainter in luminosity (e.g., Willott et al 2007Willott et al , 2010Matsuoka et al 2016Matsuoka et al , 2022Kim et al 2018Kim et al , 2020Fujimoto et al 2022); however, these samples are still far more luminous than what is observed in the nearby Universe (L bol ∼ 10 43 −10 44 erg s −1 ; e.g., Greene & Ho 2007;Liu et al 2018Liu et al , 2019, biasing our understanding of early SMBHs toward the most massive and active populations (however, see also Mezcua et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, by assuming that the feedback is inefficient at z ∼ 6 while it becomes more efficient until z ∼ 4, an evolution model that the bias keeps low until z ∼ 4 and increases rapidly to z ∼ 6 does not conflict with our observational result. Alternatively, it could be explained by intermittent black hole growth (Inayoshi et al 2022;Li et al 2023). To further restrict the models, the measurement of the bias parameter at z ∼ 5 is a key.…”
Section: Implication To Agn Feedbackmentioning
confidence: 99%